2019
DOI: 10.1002/pa.1994
|View full text |Cite
|
Sign up to set email alerts
|

The 2020 U.S. presidential election: A litmus test

Abstract: This paper provides an overview of what lies ahead of the United States in the event that Donald John Trump either lost or won a reelection bid. The uncertainty of the election outcomes is what we refer to as a litmus test. In this paper, we reflect on the ongoing events shaping the United States ahead of the 2020 presidential election and their implications on the United States. We suggest that the election provide a litmus test in shaping the politics of the United States in answering numerous questions rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Not surprisingly, it has been suggested that the 2020 U.S. election is a litmus test (Kasadha et al, 2019) on whether American democracy will begin to heal its wounds or it will plummet into further troubles.…”
Section: Michalinos Zembylas Open University Of Cyprus Cyprusmentioning
confidence: 99%
“…Not surprisingly, it has been suggested that the 2020 U.S. election is a litmus test (Kasadha et al, 2019) on whether American democracy will begin to heal its wounds or it will plummet into further troubles.…”
Section: Michalinos Zembylas Open University Of Cyprus Cyprusmentioning
confidence: 99%